METHODOLOGICAL APPROACHES TO IMPROVING THE COORDINATION ABILITIES OF YOUNG VOLLEYBALL PLAYERS (Scientific journal of the Fergana State University, 2024)
This article shows ways, methods, and a set of exercises to improve the effectiveness of training in the development of coordination abilities of young volleyball players. In addition, it is explained that working on the coordination of movements is one of the physical qualities that help to expand the technical and tactical capabilities of the athlete.